2021
DOI: 10.13057/asianjethnobiol/y040105
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study of medicinal plants used to treat human diseases in Gura Damole District, Bale Zone, Southeast Ethiopia

Abstract: Abstract. Assefa B, Megersa M, Jima TT. 2021. Ethnobotanical study of medicinal plants used to treat human diseases in Gura Damole District, Bale Zone, Southeast Ethiopia. Asian J Ethnobiol 4: 42-52. Many countries, including Ethiopia, use medicinal plants for their primary health care system. Plants have been used as a source of medicine to treat human diseases in Ethiopia. This study aimed to document medicinal plants to treat various human diseases in southeast Ethiopia's, the Gura Damole District of Oromia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Other similar studies in Ethiopia (Teka et al 2019;Assefa et al 2021) and elsewhere in the world (Chaachouay et al 2021;Khajuriaa et al 2021) have also found that Asteraceae are the major suppliers of medicinal plants. In addition, Fabaceae (Osman et al 2020;Alemneh 2021), Euphorbiaceae (Jima and Megersa 2018), Lamiaceae (Tuasha et al 2018;Tamene et al 2020), and Solanaceae (Abebe and Teferi 2021;Assen et al 2021;Wendimu et al 2021) were found to be dominant in the study conducted in South Wollo Zone of Amhara Region, Hulet Eju Enese District and Diguna Fango District of Wolaita Zone.…”
Section: Medicinal Plants Of Damot Woyde Districtmentioning
confidence: 68%
See 2 more Smart Citations
“…Other similar studies in Ethiopia (Teka et al 2019;Assefa et al 2021) and elsewhere in the world (Chaachouay et al 2021;Khajuriaa et al 2021) have also found that Asteraceae are the major suppliers of medicinal plants. In addition, Fabaceae (Osman et al 2020;Alemneh 2021), Euphorbiaceae (Jima and Megersa 2018), Lamiaceae (Tuasha et al 2018;Tamene et al 2020), and Solanaceae (Abebe and Teferi 2021;Assen et al 2021;Wendimu et al 2021) were found to be dominant in the study conducted in South Wollo Zone of Amhara Region, Hulet Eju Enese District and Diguna Fango District of Wolaita Zone.…”
Section: Medicinal Plants Of Damot Woyde Districtmentioning
confidence: 68%
“…Therefore, the three authors reported more medicinal plants than the present study. Whereas, Giday et al (2009a,b), Belayneh et al (2012), andAssefa et al (2021) reported 35, 51, and 30 species of medicinal plants, respectively. The difference in the number of medicinal plants could be due to the vegetation of the district, the number of informants involved in the study, the timing and duration of data collection, and the culture.…”
Section: Medicinal Plants Of Damot Woyde Districtmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, plant research and related indigenous knowledge should be an urgent task to protect and save the indigenous knowledge to transfer this knowledge to future generations. Many studies have been done in Ethiopia on ethnobotanical medicinal plants (Kefalew et al 2015;Yohannis et al 2018;Tefera and Kim 2018;Tibebu and Mesele 2019;Gonfa et al 2020;Assefa et al 2021;Ayalw and Merawi 2021;Megersa and Woldetsadik 2022). However, little research has been done so far in the Mojana Wadera woreda in the North Shewa zone of Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants are one of the most well-known of traditional knowledge. They provide primary health care (De Boer et al 2012;Mazengia et al 2019;Nahdi and Kurniawan 2019;Rianawati and Siswadi 2020;Assefa et al 2021). In addition, traditional medicine is an important source of health care in rural or tribal areas (Maroyi 2013;Farooq et al 2019;Az-Zahra et al 2021;Novriyanti et al 2021).…”
Section: Introductionmentioning
confidence: 99%